Ukrainian regional oikonymy: Modern state and perspectives - Redkva, Yaroslav; Lukashchuk, Michael (Editura Mega, 2022)
The article presents a review of Ukrainian regional oikonymy by examining the stages of its development as a subject, and reviewing contemporary analytical approaches. Attention is focused on the 1960s and 1970s, the period of the twentieth century that is the most prolific for the development of Ukrainian onomastics in general, and oikonymy (i.e. the study of settlement names) in particular. The next stage (1980s-present) is marked by a considerable increase in onomastic analysis of place names from different linguistic perspectives: a) etymological, b) synchronic and diachronic, c) lexico-semantic, d) structural and derivational, considering phonetic and morphological characteristics of oikonyms. The perspective of further linguistic studies allows a better understanding of processes of oikonym formation in diachrony (etymological, comparative historical, and stratigraphic approaches), and also illuminates modern tendencies in oikonyms coined both in Ukraine and the Slavic world.
Keywords: etymology, comparative historical analysis, regional analysis, derivational model, Ukrainian oikonymy